2010
DOI: 10.1103/physrevb.81.134413
|View full text |Cite
|
Sign up to set email alerts
|

Geometric magnetic frustration in theR-type ferriteSrSn2Ga1.3Cr2.7

Abstract: SrSn 2 Ga 1.3 Cr 2.7 O 11 is shown to be a strongly geometrically frustrated magnet through measurement of its temperature-dependent magnetic susceptibility and specific heat. This material, determined by powder neutron diffraction to have an R-type ferrite crystal structure, has S =3/ 2 Cr 3+ ions in isolated Kagomé planes with no magnetic ions in the intermediary structural layers. The Kagomé planes contain 10% nonmagnetic Ga 3+ . This structure type makes the chromate family of frustrated magnets unusual be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results of all the 3 /mmc to P6 3 /m has been observed due to ruthenium pairing in the kagome network[18][19][20]. Here, neither such phenomenon nor 2d sites splitting[13,26], i.e., a reduction of symmetry from P6 3 /mmc to P6 3 mc due to tetragonal bipyramid splitting to two tetrahedra, has been detected. On the one hand, TableIshows that the 2a (A site), 6g, and 2d sites occupancy are relatively similar for the three oxides, within 6% at most.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The results of all the 3 /mmc to P6 3 /m has been observed due to ruthenium pairing in the kagome network[18][19][20]. Here, neither such phenomenon nor 2d sites splitting[13,26], i.e., a reduction of symmetry from P6 3 /mmc to P6 3 mc due to tetragonal bipyramid splitting to two tetrahedra, has been detected. On the one hand, TableIshows that the 2a (A site), 6g, and 2d sites occupancy are relatively similar for the three oxides, within 6% at most.…”
mentioning
confidence: 66%
“…The valencies determined 72 from x-ray diffraction and charge-balance calculations are re-73 ported to be Mn 3+ [14], Co 2+ or Fe 2+ /Fe 3+ , and Ru 3+ /Ru 5+ 74 [25]. In BaMRu 5 O 11 , the face-shared site contains Ru 4+ cal-75 culated from bond valence sum while the valency is closer 76 to 3.8 in the kagome lattice [14], and recent x-ray absorption 77 These materials present a rich variety of properties with frustrated magnetism arising from the kagome lattice as reported in BaZnRu 5 O 11 [18], in SrNiRu 5 O 11 [20], or in SrSn 2 Ga 1.3 Cr 2.7 O 11 [26], and possible spintronic applications for metallic and ferrimagnetic materials in SrCo 1.89 Ru 4.11 O 11 [16] or in BaFe 2±x Ru 4∓x O 11 [27]. The complex magnetic structure of BaFe 2±x Ru 4∓x O 11 with spin chirality in the kagome planes leads to a strong anomalous Hall effect [27].…”
Section: Introductionmentioning
confidence: 96%
“…To date the successful synthesis of ideal SrCr 9 Ga 3 O 19 has yet to be achieved; in the limiting composition of SrCr 8.8 Ga 3.2 O 19 ∼ 2% of the Cr 3+ sites are occupied by non-magnetic Ga 3+ [8]. A deficiency of Cr 3+ in the layered ferrite materials is not unique to SCGO; in both Ba 2 Sn 2 ZnGa 3 Cr 7 O 22 (BSZGCO, a QS-type ferrite) [16,17] and SrSn 2 Ga 1.3 Cr 2.7 O 11 (SSGCO, an R-type ferrite) [18] deficiencies of Cr 3+ on the kagome plane of 3% and 10%, respectively, are observed. The Ga-rich end of the SCGO compositional series has been extensively studied and it has been shown that Ga fully occupies the tetrahedral and trigonal bipyramidal sites, with Ga and Cr disordered over the octahedral sites [5,6,8,10].…”
Section: Introductionmentioning
confidence: 99%